In fact, it is a similar question to $$\frac{1}{1}+\frac{1}{2}+\frac{1}{3}+\cdots+\frac{1}{(p-1)}$$ However, this question has some changes in the sign. ($p$ is an odd prime)

My thought is that I tried $$\frac{1}{1}+\frac{1}{2}+\frac{1}{3}+\cdots+\frac{1}{(p-1)}-2\cdot(\frac{1}{2}+\frac{1}{4}+\frac{1}{6}+\cdots+\frac{1}{(p-1)})$$ The First half can be written as $\frac{\sigma_{p-2}}{\sigma_{p-1}}$. While the second half I am not sure how to convert into a sigma notation since when I multiply $2$ into the parenthesis, I am not sure what is the ending.

Any suggestions or methods to continue? Or, there is another better way to do it?

  • $\begingroup$ yes, sorry for some typo $\endgroup$ – Jason Ng Oct 19 '18 at 15:15

$$(1+1)^p-2=\sum_{r=1}^{p-1}\binom pr$$

Now for $\displaystyle1\le r\le p-1,\binom pr=\dfrac pr\binom{p-1}{r-1}$

$\displaystyle\implies\dfrac{(1+1)^p-2}p\equiv\sum_{r=1}^{p-1}\dfrac1r\binom{p-1}{r-1}\pmod p$

Finally $\displaystyle\binom{p-1}{r-1}=\prod_{m=1}^{r-1}\dfrac{p-1-(m-1)}{m}\equiv(-1)^{r-1}\pmod p$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.